Monopolar radiofrequency for reposing drooping fat planes and facial rejuvenation: A prospective study on 30 subjects towards true antiaging - Garg, Suruchi; Vashisht, Kanya Rani; Sushruth, P. Ram; Saka, Deepa V. (Journal of cosmetic dermatology, 2022)
Background Monopolar radiofrequency (MRF) for facial rejuvenation works by diffusely heating the dermis and subdermal fibro‐septal network. Immediate collagen contraction and long‐term neo‐collagenesis produce antiaging effects. Aim To lift and repose drooping fat planes along their vectors of descent to restore natural, youthful contours using MRF and to objectively measure, quantify, and analyze the antiaging effects of MRF on the backdrop of functional facial anatomy. Methods This was a prospective study on 30 subjects aged 25–65 years who underwent three sessions of MRF (Exilis, BTL Aesthetics) with a modified protocol at weekly intervals. Clinical evaluation at baseline and 4 weeks after the final session was done according to the global drooping and wrinkles classification and scoring system (GDWCSS) and statistically evaluated. Two patients were analyzed with Ultrasound and Vectra‐H1 imaging for change in subcutaneous fat depth and volume over different facial areas, respectively. Results There was improvement in all parameters (volume alteration and wrinkles) of the GDWCSS, of which improvement in cases that had baseline severe (grade‐4) temporal fat loss, malar fat loss, periorbital hollowing, and puffiness was statistically significant. The results of imaging supported the clinical findings. Conclusion Monopolar radiofrequency targets facial collagen as deep as the facial fat, thereby achieving “reversal” of the grooves and bulges of aging with volume re‐distribution and favorable “remolding” of fat pads. The result is simultaneous skin tightening, lifting and contouring in manner that is natural, regenerative, and corrective. Given its versatility, efficacy, safety, and tolerability, it is emerging as a power‐player in the dermatologist's antiaging armamentarium.